Association of cholesterol level with dopamine loss and motor deficits in Parkinson disease: A cross‐sectional study. (25th October 2022) - Jeong, Seong Ho; Lee, Hye Sun; Chung, Seok Jong; Yoo, Han Soo; Jung, Jin Ho; Baik, Kyoungwon; Baik, Jong Sam; Sohn, Young H.; Lee, Phil Hyu
Abstract: Background and purpose: Cholesterol is vital in neuronal function; however, the influence of cholesterol levels on parkinsonism is unclear. This study investigated the relationship between baseline total cholesterol (TC) levels, dopamine loss, and motor symptoms in drug‐naïve Parkinson disease (PD). Methods: This cross‐sectional study enrolled 447 drug‐naïve patients with PD who underwent dopamine transporter (DAT) imaging. Multivariate linear regression was used to investigate the effect of cholesterol levels on Unified Parkinson's Disease Rating Scale Part III (UPDRS‐III) total score and each subscore after adjusting for the covariates. An interaction analysis was performed to examine the interaction between TC levels and statin use on the UPDRS‐III scores. Results: No significant correlation was found between TC levels and DAT availability after adjusting for potential confounders. Multivariate linear regression showed that TC levels were significantly and negatively associated with the UPDRS‐III total score ( β  = −0.116, p  = 0.013) and bradykinesia subscore ( β  = −0.145, p  = 0.011). Dichotomized analysis according to TC levels showed that TC levels were significantly associated with UPDRS‐III total score, and rigidity, bradykinesia, and axial subscores only in the low TC group. There was an interaction effect between TC levels and statin use for the axial subscores ( β  = −0.523, p  = 0.025). Subgroup analysis showed that TC levels were significantly and negatively associated with the axial subscore in statin users; however, no association was found in statin nonusers. Conclusions: This study suggests that TC levels affect parkinsonian motor symptoms, especially in subjects with low cholesterol status, whereas the severity of axial motor symptoms is negatively associated with TC levels only in statin users. Abstract : These results indicate that cholesterol levels are significantly and independently associated with the severity of parkinsonian motor deficits irrespective of nigrostriatal dopaminergic neuronal loss. Also, cholesterol‐lowering statins may have a detrimental effect on axial motor symptoms in patients with Parkinson disease.